Gastroesophageal reflux and asthma: when, how, and why. Issue 1 (February 2021) - Paoletti, Giovanni; Melone, Giulio; Ferri, Sebastian; Puggioni, Francesca; Baiardini, Ilaria; Racca, Francesca; Canonica, Giorgio W.; Heffler, Enrico; Malipiero, Giacomo
Abstract : Purpose of review: Gastro-esophageal reflux is a possible cause of uncontrolled symptoms of asthma and should be actively investigated and treated before severe asthma is diagnosed and biological therapy started. Recent findings: Recent investigations on esophageal function and tissue biomarkers in patients with asthma and associated GERD have established a relevant role for esophageal motility and neuronal sensory abnormalities in linking the two diseases. Characterization of the underpinning inflammatory substrate has showed mixed results as both neutrophilic and eosinophilic type 2 inflammatory changes have been described. Summary: New findings regarding inflammatory mechanisms in GERD-associated asthma as well as new diagnostic tools to investigate functional esophageal abnormalities and characterize asthma endotype have identified potential treatable traits that may improve the clinical management and outcome of asthmatic patients with GERD.